DNA profiling success rates of commonly submitted crime scene items. Issue 1 (December 2019) - Wong, Hang Yee; Tan, Jiayu; Lim, Zi Gui; Kwok, Rachel; Lim, Wilson; Syn, Christopher Kiu-Choong
Abstract: Advances in forensic DNA profiling have facilitated the generation of DNA profiles from trace (touch/contact) articles. This pilot study aimed to examine the DNA profiling success of such articles which may be unique to our local scene, as well as to compare results of common articles in published literature. Casework data from 1122 commonly submitted trace articles were analysed. The articles were grouped into 18 categories and were classified into high/low-success articles based on the success rate of obtaining a DNA profile from those articles. The DNA profiling success rate of common articles were generally comparable with published literature, with exception being those that were unique to the local scene, such as adhesive tape bundle. The results of this study can guide law enforcement officers towards identification and prioritisation of crime scene items for DNA analysis, allowing for more effective utilisation of resources.